Validity and reliability of the Turkish version of Exercise Benefits/ Barriers Scale: Perceived exercise benefits and barriers of patients with different axial spondyloarthritis subtypes - Devrim Can Sarac; Elif Durak Ediboglu; Derya Ozer Kaya; Gozde Duran; Emre Alp Akatay; Sercan Gucenmez; Servet Akar; Deniz Bayraktar (Archives of Rheumatology, 2024)
Objectives: The aim of this study was to translate the Exercise Benefits/Barriers Scale (EBBS) into Turkish and investigate the perceptions of Turkish-speaking patients with different axial spondyloarthritis (axSpA) subtypes regarding exercise benefits and barriers. Patients and methods: This validation study was conducted between June 2018 and December 2021. Patients with axSpA were consecutively assessed regarding physical (age, sex and body mass index) and disease-related characteristics (disease activity, spinal mobility, functional status, quality of life, health status, emotional status, and kinesiophobia). Eligible participants were asked to complete the EBSS and other outcome measurements during their initial visits. EBBS was readministered 7 to 14 days later. Results: One hundred forty-eight patients (89 males, 59 females; mean age: 44.3±11.8 years; range, 19 to 65 years) were included in the study. Of the patients, 108 had radiographic axSpA, and 40 had nonradiographic axSpA. EBBS-Barriers and EBBS-Benefits subscales demonstrated adequate internal consistency (Cronbach’s alphas of 0.82 and 0.95, respectively) and test-retest reliability (intraclass correlation coefficients of 0.837 and 0.807, respectively). No significant differences were observed between axSpA subtypes regarding EBBS-Barriers (p=0.12) and EBBS-Benefits (p=0.10) subscales. Significant relationships were detected between kinesiophobia and EBBS-Barriers scores (r=–0.424, p<0.01), as well as EBBS-Benefits scores (r=–0.344, p<0.01) for all patients. EBBS-Benefits scores were correlated to health status (r=–0.412, p=0.08) and quality of life (r=–0.394, p=0.01) in patients with nonradiographic axSpA. Conclusion: According to our results, the Turkish EBBS is a valid and reliable tool for patients with axSpA. Perceptions of the patients with axSpA regarding exercise barriers and benefits do not differ according to the disease subtype. It appears that kinesiophobia may be an important parameter regarding exercise perception in axSpA.